Treating chronic lymphocytic leukemia with obinutuzumab: safety and efficacy considerations. Issue 6 (2nd June 2016) - Reda, G.; Orofino, N.; Cassin, R.; Sciumè, M.; Fattizzo, B.; Cortelezzi, A.
ABSTRACT: Introduction : Obinutuzumab is a novel glycoengineered type II anti-CD20 monoclonal antibody (MoAb) with a higher affinity for CD20 epitope. It was approved by the United States Food and Drug Administration (FDA) in November 2013 for use in combination with chlorambucil for previously untreated chronic lymphocytic leukemia (CLL). Areas covered : This article evaluates the safety of obinutuzumab in CLL patients, also addressing pharmacokinetics/pharmacodynamics (PK/PD), clinical use and efficacy. Moreover, a comparison with other anti-CD20 MoAb is performed. The principal available studies on obinutuzumab are reviewed, focusing on CLL. A PubMed literature search (August 2002 to September 2015) was conducted using the terms obinutuzumab, GA101, anti-CD 20 antibody, and CLL . Expert opinion : Obinutuzumab, a third-generation anti-CD20 MoAb, is a safe and effective treatment for elderly patients who are un-fit for fludarabine-based regimen. Its use, proven in the CLL11 study and the results of many ongoing trials evaluating other obinutuzumab-based regimen can lead obinutuzumab to be a candidate to replace rituximab as the first-line treatment option.